2001
DOI: 10.1002/1521-3757(20010302)113:5<970::aid-ange970>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Membrane Photolabeling of the Transmembrane Domain of Glycophorin A in Phospholipid Vesicles

Abstract: The topography of membrane-bound proteins at atomic resolution is known only in rare cases. [1] Although the primary amino-acid sequence of glycophorin A (GPA), the major sialoglycoprotein of the human erythrocytes, has been known for more than twenty years and was the first membrane protein sequence elucidated, [2] a three-dimensional picture of the protein is still missing. We have previously developed the photoactivable membrane probe 1. This is a phospholipid with two distal, polar heads (a bola-amphiphil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, this technique requires the protein to have suitable mobility in the bilayer: mobile peptides have inefficient magnetization transfer rates from the lipids. Beyond NMR, electron paramagnetic resonance spectroscopy and optical spectroscopic methods such as fluorescence resonance energy transfer are well established for investigating the depth of insertion of membrane peptides (Altenbach et al, 1994;Lakey et al, 1993;Ogawa et al, 2001;Shin et al, 1993). However, these approaches require the use of bulky and often dynamic spin probes, which complicate the extraction of the immersion depth.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique requires the protein to have suitable mobility in the bilayer: mobile peptides have inefficient magnetization transfer rates from the lipids. Beyond NMR, electron paramagnetic resonance spectroscopy and optical spectroscopic methods such as fluorescence resonance energy transfer are well established for investigating the depth of insertion of membrane peptides (Altenbach et al, 1994;Lakey et al, 1993;Ogawa et al, 2001;Shin et al, 1993). However, these approaches require the use of bulky and often dynamic spin probes, which complicate the extraction of the immersion depth.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that most of the cross-linking involved the carboxyl group of Glu 70 , thus suggesting that this residue was located within the bilayer 23 . However, twenty years later the group of Nakatani used the same approach with a different lipid probe and obtained very different results 24,25 . They used a benzophenonebased bola-phospholipid probe (10, Figure 2), thus guaranteeing that the label was located at the center of bilayer, with no possibility for looping back.…”
Section: Alamethicinmentioning
confidence: 99%
“…FTIR (NaCl, cm -1 ): 3005, 2978, 2931, 2250, 1703, 1693, 1618, 1492, 1446, 1390, 1296, 1247, 1132 under normal conditions, the arylation or olefination products resulting from olefins with electron-rich substituents usually give rise to a mixture of both the α-and β-substituted regioisomeric olefins. 117 The regioselectivity of the Heck reaction has remained a hot research topic for many years.…”
Section: Mechanism Studymentioning
confidence: 99%